Using Birth Cohort Data to Assess the Impact of the UK 2008–2010 Economic Recession on Smoking During Pregnancy. Issue 8 (7th May 2018) - Uphoff, Eleonora P; Small, Neil; Pickett, Kate E
Abstract: Introduction: Despite the well-known link between stress and smoking, evidence for associations between economic recession, financial stress, and smoking is contradictory. In this study, we assess whether women were more likely to continue smoking during pregnancy if they were exposed to the UK 2008–2010 economic recession during pregnancy than those who were unexposed, and whether this relationship is mediated by financial stress. Methods: We used cross-sectional data on 2775 pregnant women who were regular smokers before pregnancy and who were enrolled in the UK Born in Bradford cohort study between March 2007 and December 2010. The cutoff date for exposure to recession was set as August 1, 2008, based on local and national economic data. Multivariable logistic regression analysis included potential confounders: maternal age, parity, cohabitation, ethnicity, and maternal age. The mediating role of financial stress was analyzed using "worse off financially" and a "difficult financial situation" as indicators of financial stress in Sobel–Goodman mediation tests with bootstrap resampling. Results: After taking into account potential confounders, exposure to recession was associated with continued smoking during pregnancy ( OR = 1.19, 95% CI = 1.01 to 1.41, p = 0.03). A worse financial situation and a difficult financial situation were identified as mediators, explaining 8.4% and 17.6%, respectively, of the relationship between exposure to recession and smoking during pregnancy. Conclusions: Smoking during pregnancy is associated with exposure to the UK 2008–2010 economic recession during pregnancy, and this relationship is partly mediated by financial stress. Implications: Health inequalities in smoking during pregnancy are affected by economic recession, as those who are most likely to smoke are also most likely to experience the financial stress resulting from economic recession. Socioeconomic conditions at the societal and individual level are important targets when aiming to reduce rates of smoking during pregnancy.